DNA methylation profile in chronic myelomonocytic leukemia associates with distinct clinical, biological and genetic features. Issue 1 (2nd January 2018) - Palomo, Laura; Malinverni, Roberto; Cabezón, Marta; Xicoy, Blanca; Arnan, Montserrat; Coll, Rosa; Pomares, Helena; García, Olga; Fuster-Tormo, Francisco; Grau, Javier; Feliu, Evarist; Solé, Francesc; et al.
ABSTRACT: Chromosomal abnormalities are detected in 20–30% of patients with chronic myelomonocytic leukemia (CMML) and correlate with prognosis. On the mutation level, disruptive alterations are particularly frequent in chromatin regulatory genes. However, little is known about the consequential alterations in the epigenetic marking of the genome. Here, we report the analysis of genomic DNA methylation patterns of 64 CMML patients and 10 healthy controls, using a DNA methylation microarray focused on promoter regions. Differential methylation analysis between patients and controls allowed us to identify abnormalities in DNA methylation, including hypermethylation of specific genes and large genome regions with aberrant DNA methylation. Unsupervised hierarchical cluster analysis identified two main clusters that associated with the clinical, biological, and genetic features of patients. Group 1 was enriched in patients with adverse clinical and biological characteristics and poorer overall and progression-free survival. In addition, significant differences in DNA methylation were observed between patients with low risk and intermediate/high risk karyotypes and between TET2 mutant and wild type patients. Taken together, our results demonstrate that altered DNA methylation patterns reflect the CMML disease state and allow to identify patient groups with distinct clinical features.